Letter from Charles C. Post to James Curtis Booth, September 23, 1854 - Post, Charles C. (1854)
Charles C. Post, a cousin of James Curtis Booth (1810-1888) writes to Booth to discuss the health of Post's wife and child.
Keywords: Booth, James Curtis, 1810-1888